2021
DOI: 10.3390/pathophysiology28030023
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of TLK1 and AKTIP as a Potential Regulator of AKT Activation in Castration-Resistant Prostate Cancer Progression

Abstract: Prostate cancer (PCa) progression is characterized by the emergence of resistance to androgen deprivation therapy (ADT). AKT/PKB has been directly implicated in PCa progression, often due to the loss of PTEN and activation of PI3K>PDK1>AKT signaling. However, the regulatory network of AKT remains incompletely defined. Here, we describe the functional significance of AKTIP in PCa cell growth. AKTIP, identified in an interactome analysis as a substrate of TLK1B (that itself is elevated following ADT), enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…The same may not be said for mice treated with J54, which showed few proliferating cells even in the small patches of micro-metastases. This can readily be explained by the fact that J54, inhibitor of TLK1, could affect additional cancerous pathways that are regulated by this kinase, such as the TLK1>NEK1>YAP nexus (17) or the AKTIP>AKT (18) pathway, thus resulting in overall suppression of tumors growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same may not be said for mice treated with J54, which showed few proliferating cells even in the small patches of micro-metastases. This can readily be explained by the fact that J54, inhibitor of TLK1, could affect additional cancerous pathways that are regulated by this kinase, such as the TLK1>NEK1>YAP nexus (17) or the AKTIP>AKT (18) pathway, thus resulting in overall suppression of tumors growth.…”
Section: Resultsmentioning
confidence: 99%
“…TLK1's role in driving PCa progression is an active pursuit of our lab. We have demonstrated that TLK1 can promote androgen dependent to androgen independent progression and survival of PCa cells through various mechanisms such as hyperactivating NEK1 and NEK1 mediated activation of ATR>Chk1, VDAC1, stabilization of YAP1 or by regulating AKT through AKTIP phosphorylation (13)(14)(15)(16)(17)(18). TLK1 driven motility promotion of PCa cells was a novel finding from our lab, although it was known that TLK2, a closely related kinase of TLK1 (both shares 96% homology in their kinase domain and 84% overall homology), can increase the migration and invasion of breast cancer and glioblastoma cell lines (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…[57] ). NEK1 can phosphorylate VDAC1 on S193 residue controlling its gatekeeping activity [58] . We demonstrated that disruption of TLK1>NEK1 axis sensitizes the PCa cells to low doses of doxorubicin treatment by reducing VDAC1 S193 phosphorylation and its stability.…”
Section: Role Of Tlk1 In Other Pathwaysmentioning
confidence: 99%
“…TLK1 mediates anti-apoptotic responses through AKT activation by interacting and phosphorylating AKT interacting protein (AKTIP). TLK1 phosphorylation of AKTIP on T22 and S237 residues increases its scaffolding activity to anchor both AKT and PDK1 to the phosphatidylinositol (3,4,5)-trisphosphate (PIP3) regions of the plasma membrane where PDK1 can phosphorylate AKT on T308 residue followed by S473 phosphorylation by mTORC2 complex for full activation of AKT [ 59 ] . Fully activated AKT may relay pro-survival signals by inhibiting BAD, caspase 9, and FoxO3 pro-apoptotic factors through phosphorylation facilitating CRPC progression.…”
Section: Role Of Tlk1 In Other Pathwaysmentioning
confidence: 99%
“…TLK1′s role in driving PCa progression is an active pursuit of our lab. We have demonstrated that TLK1 can promote androgen-dependent to androgen-independent progression and survival of PCa cells through various mechanisms, such as hyperactivating NEK1 and NEK1-mediated activation of ATR > Chk1 or VDAC1, stabilization of YAP1, or by directly regulating AKT through AKTIP phosphorylation [ 13 , 14 , 15 , 16 , 17 , 18 ]. TLK1-driven motility promotion of PCa cells was a novel finding from our lab, although it was known that TLK2, a closely related kinase of TLK1 (both shares 96% homology in their kinase domain and 84% overall homology), can increase the migration and invasion of breast cancer and glioblastoma cell lines [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%